Direct intramyocardial injection of VEGF mRNA in patients undergoing coronary artery bypass grafting - Anttila Vesa; Saraste Antti; Knuuti Juhani; Hedman Marja; Jaakkola Pekka; Laugwitz Karl-Ludwig; Krane Markus; Jeppsson Anders; Sillanmäki Saara; Rosenmeier Jaya; Zingmark Pernilla; Rudvik Anna; et al. (United States, 2025)
Vascular endothelial growth factor A (VEGF-A) has therapeutic cardiovascular effects, but delivery challenges have impeded clinical development. We report the first clinical study of naked mRNA encoding VEGF-A (AZD8601) injected into the human heart. EPICCURE (ClinicalTrials.gov: NCT03370887) was a randomized, double-blind study of AZD8601 in patients with left ventricular ejection fraction (LVEF) 30%-50% who were undergoing elective coronary artery bypass surgery. Thirty epicardial injections of AZD8601 (total 3 mg) or placebo in citrate-buffered saline were targeted to ischemic but viable myocardial regions mapped using quantitative [15O]-water positron emission tomography. Seven patients received AZD8601 and four received placebo and were followed for 6 months. There were no deaths or treatment-related serious adverse events and no AZD8601-associated infections, immune reactions, or arrhythmias. Exploratory outcomes indicated potential improvement in LVEF, Kansas City Cardiomyopathy Questionnaire scores, and N-terminal pro-B-type natriuretic peptide levels, but the study is limited in size, and significant efficacy conclusions are not possible from the dataset. Naked mRNA without lipid encapsulation may provide a safe delivery platform for introducing genetic material to cardiac muscle, but further studies are needed to confirm efficacy and safety in a larger patient pool.